RETRACTED: Farm typology analysis in Russian regions with different small entrepreneurship development level - Ukolova Anna; Ulianckin Alexandr (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001